CIRRHOSIS OF THE LIVER CAUSED BY EXCESS DIETARY CYSTINE - Earle, David P. (The Rockefeller University Press, 1941)
1. Cystine fed to young albino rats as 10 per cent of the diet resulted in: (a) Portal hemorrhagic necrosis, resembling eclampsia, within 3 or 4 days. (b) A high mortality rate. (c) Fatty infiltration of hepatic cells in all rats surviving the initial acute lesion. (d) Cirrhosis of the liver in rats surviving more than 2 weeks. 2. 5 per cent dietary cystine produced marked fatty infiltration of the liver, followed by portal hemorrhagic necrosis. Cirrhosis was present in one of the two rats on the diet for 6 weeks. 3. The livers of rats fed 5 or 10 per cent cystine diets followed by the McCollum stock diet, showed evidence of residual cellular damage, and of regeneration as shown by mitotic figures. 4. In this series of 30 rats on excess dietary cystine, a renal lesion was found in only one case.